Both de novo synthetized and exogenous fatty acids support the growth of hepatocellular carcinoma cells. (6th July 2016) - Cao, Dan; Song, Xinhua; Che, Li; Li, Xiaolei; Pilo, Maria G.; Vidili, Gianpaolo; Porcu, Alberto; Solinas, Antonio; Cigliano, Antonio; Pes, Giovanni M.; Ribback, Silvia; Dombrowski, Frank; et al.
Abstract: Background & Aims: Although it is well established that fatty acids (FA) are indispensable for the proliferation and survival of cancer cells in hepatocellular carcinoma (HCC), inhibition of Fatty Acid Synthase (FASN) cannot completely repress HCC cell growth in culture. Thus, we hypothesized that uptake of exogenous FA by cancer cells might play an important role in the development and progression of HCC. Lipoprotein lipase (LPL) is the enzyme that catalyses the hydrolysis of triglycerides into free fatty acids (FFA) and increases the cellular uptake of FA. Methods: We used immunohistochemistry and quantitative reverse transcription real‐time polymerase chain reaction to evaluate LPL expression in human and mouse HCC samples. Using lipoprotein‐deficient medium as well as siRNAs against LPL and/or FASN, we investigated whether human HCC cells depend on both endogenous and exogenous fatty acids for survival in vitro . Results: We found that LPL is upregulated in mouse and human HCC samples. High expression of LPL in human HCC samples is associated with poor prognosis. In HCC cell lines, silencing of FASN or LPL or culturing the cells in lipoprotein‐deficient medium significantly decreased cell proliferation. Importantly, when FASN suppression was coupled to concomitant LPL depletion, the growth restraint of cell lines was further augmented. Conclusions: The present study strongly suggests that both de novo synthetized and exogenous FA play a major role along hepatocarcinogenesis. Thus, combined suppression of LPL and FASN might be highly beneficial for the treatment of human HCC.